Measuring CP violation and B-s(0)-(B)over-bar(s)(0) mixing using B-s(0) -> J/psi phi with phi -> K+K-, J/psi -> mu(+)mu(-) - Azfar, F; Huffman, T; Lyons, L; Reichold, A; Waters, D (2000)
We present a preliminary study of a new technique for measuring B-s(0) mixing and CP violation using the decay Bs0 --> J/phi phi, phi --> K+K-, J/phi --> mu(+)mu(-). This technique utilizes the unequal lifetimes of the B-s(0) CP even and odd eigenstates, and an angular variable decomposition of the CP content of the final state. This study is based on CDF Run-I observations and Run-II projections, and predicts that the B-s(0) mixing parameter x(s) can be measured with high accuracy in untagged samples if this approach is adopted. A large CP asymmetry may also be possible to measure. The accuracy of this method is shown to increase for higher values of x(s) as the lifetime splitting of the CP eigenstates increases. The measurement of x(s) does nor depend on tagging, whereas the observation of a CP-violating asymmetry does.